2012
DOI: 10.1038/aps.2011.189
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 overexpression protects murine osteoblasts against TNF-α-induced injury in vitro by suppressing the NF-κB signaling pathway

Abstract: Aim: Sirtuin 1 (Sirt1) is the class III histone/protein deacetylase that interferes with the NF-κB signaling pathway, thereby has antiinflammatory function. This study was undertaken to investigate whether Sirt1 could protect osteoblasts against TNF-α-induced injury in vitro. Methods: Murine osteoblastic cell line, MC3T3-E1, was used. Overexpress of Sirt1 protein in MC3T3-E1 cells was made by transfection the cells with Sirt1-overexpressing adenovirus. The levels of mRNAs and proteins were determined with qRT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…41 For example, SIRT1 was able to activate runt-related transcription factor 2 (RUNX2) and suppress NF-κB signaling in bone, leading to the stimulation of osteoblastogenesis and the inhibition of osteoclastogenesis. [42][43][44][45] In this study, the expression of SIRT1 was decreased in macrophages treated …”
Section: Discussionmentioning
confidence: 92%
“…41 For example, SIRT1 was able to activate runt-related transcription factor 2 (RUNX2) and suppress NF-κB signaling in bone, leading to the stimulation of osteoblastogenesis and the inhibition of osteoclastogenesis. [42][43][44][45] In this study, the expression of SIRT1 was decreased in macrophages treated …”
Section: Discussionmentioning
confidence: 92%
“…However, when exposed to risk factors, such as smoking or ageing, Sirt3 knockout mice will have high oxidative stress level and may be more sensitive to osteoporosis Among the Sirtuin family, Sirt1, Sirt2, and Sirt6 are reported to regulate bone homeostasis in vivo [24][25][26]. Sirt1 regulates differentiation of MSCs and represses osteoblast injury [27,28], while Sirt2 and Sirt6 protect mice from arthritis [25,26]. Sirt3 is the first mitochondrial Sirtuin that has been shown to participate in maintaining bone hemostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that SIRT1 action is not limited to epigenetic mechanisms as it exerts its multiple activities by interacting not only with histones but also with numerous transcription factors, enzymes and other protein species [52]. Additional studies, for example, have shown that SIRT1 promotes the activation of RUNX2 and the suppression of NFκB signaling, thus stimulating osteoblastogenesis while also inhibiting osteoclastogenesis; this indicates that it plays an important role in the coupling of bone formation and resorption with a possible contribution to bone quality and a reduction in bone frailty ( Figure 4) [51,[53][54][55].…”
Section: Sirtuin 1 As An Important Regulator Of Bone Homeostasismentioning
confidence: 99%
“…In the bone environment, SIRT1 causes the deacetylation of histones at the SOST promoter, thus repressing SOST expression and preventing its negative regulation of osteoblast activity. In addition, SIRT1 promotes the activation of RUNX2 and suppression of NFκB signaling, thereby both stimulating osteoblastogenesis and inhibiting osteoclastogenesis [51,[53][54][55]. It is also positively linked to estrogen signaling, an essential regulator of bone mass, both upstream and downstream of the estrogen receptor.…”
Section: Mirnas In Osteoblast Differentiationmentioning
confidence: 99%